Penggunaan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Minat dan Hasil Belajar IPS Siswa Kelas VI SDN 1 Tameng Tahun 2018/2019 - Pujiono, Pujiono (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study is to explain the learning process using the Jigsaw type cooperative model to increase the interest and learning outcomes IPS of sixth graders at SDN 1 Tameng in 2018/2019. This research is a quantitative research. This research is designed in 2 cycles, each cycle includes stages: planning, implementation, observation, and reflection. The data on the written test of learning outcomes were analyzed until the results could reach the limit of completion, namely a minimum average of 75, a minimum of 80% of students scored 75 or more as the limit for completion of the written test of learning outcomes. The research carried out obtained the results of the average student interest in the initial condition of 59,33%, in the final condition it became 81%. The learning outcomes test in the initial condition was 67.08 with a completeness level of 41.67%, in the final condition, the average was 81.67 with a completeness level of 83,33%. Based on the actions, it can be concluded: The implementation of the learning process according to the steps of the Jigsaw cooperative model can increase the interest and learning outcomes IPS of sixth graders at SDN 1 Tameng in 2018/2019.